Key performance indicators for stroke from the Ministry of Health of Brazil: benchmarking and indicator parameters - Lange, Marcos C; Braga, Gabriel Pereira; Nóvak, Edison M; Harger, Rodrigo; Felippe, Maria Justina Dalla Bernardina; Canever, Mariana; Dall’Asta, Isabella; Rauen, Jordana; Bazan, Rodrigo; Zetola, Viviane (Arquivos de Neuro-Psiquiatria, 2017)
The present study aimed to analyze the stroke units in two centers for the key performance indicators (KPIs) required by the Ministry of Health in Brazil. All 16 KPIs were analyzed, including the percentage of patients admitted to the stroke unit, venous thromboembolism prophylaxis in the first 48 hours after admission, pneumonia and hospital mortality due to stroke, and hospital discharge on antithrombotic therapy in patients without cardioembolic mechanism.Both centers admitted over 80% of the patients in their stroke unit. The incidence of venous thromboembolism prophylaxis was > 85%, that of in-hospital pneumonia was < 13%, the hospital mortality for stroke was < 15%, and the hospital discharge on antithrombotic therapy was > 70%.Our results suggest using the parameters of all of the 16 KPIs required by the Ministry of Health of Brazil, and the present results for the two stroke units for future benchmarking.
Keywords: stroke; quality indicators, health care; delivery healthcare; outcome and process assessment; health care